REPRESENTASI STIGMA ISU KESEHATAN MENTAL DAN UPAYA PEMATAHANNYA DALAM DRAMA KOREA DAILY DOSE OF SUNSHINE - Yesha Marito Febriani Banjarnahor; Joyo Nur Suryanto Gono (Interaksi Online, 2026)
Mental health stigma is one of the social issues found in society. Stigma is formed through prejudice, stereotypes, rejection, and discrimination experienced by individuals within their social environment. The Korean drama Daily Dose of Sunshine is an audiovisual medium that serves as a platform for representing mental health issues to the public. This study employed a descriptive qualitative approach within an interpretive paradigm and utilized John Fiske’s semiotic analysis, which consists of the levels of reality, representation, and ideology. The research data were obtained through observations of dialogues, scenes, and interactions among characters that represent mental health stigma in the drama Daily Dose of Sunshine. The findings reveal that the representation of mental health stigma in the drama is portrayed through various forms of fear and prejudice, labeling and stereotyping, as well as rejection and discrimination toward individuals experiencing mental disorders or those with a history of mental illness. These representations are constructed through dialogues, scenes, and interactions among characters that reflect society’s negative perceptions of mental health issues.